Pengaruh Suasana Kafe dan Promosi Terhadap Keputusan Pembelian : Ajudan Kopi Karawang - Trisakti, Muhamad Noufal; Arnu, Anggi Pasca (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research was conducted with the aim of knowing how much influence the cafe atmosphere and promotions have on purchasing decisions at the Karawang Coffee Aide Cafe. This research method uses quantitative methods with descriptive verification. The data collection technique used in this study is primary data obtained through questionnaires. The population of this study were visitors to the Karawang coffee aide cafe through a survey totaling 366 people in 2022. This study used a significance level of 10% for a sample calculation of 100 people who were determined using a purposive sampling technique. This study uses path analysis to determine how much influence the cafe atmosphere and promotions have on purchasing decisions.The results of the correlation analysis between the atmosphere of the cafe and purchasing decisions get a value of 0.0824, meaning that both have a strong correlation with a positive and one-way relationship of 82.4%. The partial test results of the atmosphere of the cafe on purchasing decisions with a path coefficient value of 55.7% and the calculation of the coefficient of determination is 31.02%, this shows that the atmosphere of the cafe has a partial influence on purchasing decisions of 31.02%. While the promotion variable has a path coefficient value of 26.4% and the calculation of the determination coefficient is 6.96%. this shows that promotion has a partial effect on purchasing decisions of 6.96% while the remaining 93.04% is influenced by other variables not examined. The results of the hypothesis testing of the influence of cafe atmosphere and promotions on purchasing decisions simultaneously have an effect of 0.5388 or 53.88% while the influence of other variables outside the model is 0.4612 or 46.12%. Keywords: Cafe atmosphere, Promotion, Purchase Decision.